2020
DOI: 10.5713/ajas.19.0190
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fit of automatic milking system and test-day records with the use of lactation curves

Abstract: Objective: The aim of the paper was to compare the fit of data derived from daily automatic milking systems (AMS) and monthly test-day records with the use of lactation curves; data was analysed separately for primiparas and multiparas.Methods: The study was carried out on three Polish Holstein-Friesians (PHF) dairy herds. The farms were equipped with an automatic milking system which provided information on milking performance throughout lactation. Once a month cows were also subjected to test-day milkings (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…The differences reported in other studies may be explained by different breeds and farming conditions. Different values of peak yield and day of peak was described by many authors [1,2,5,7,14]. 37 % of the total milk yield) was produced in the period between 306 and 547 days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The differences reported in other studies may be explained by different breeds and farming conditions. Different values of peak yield and day of peak was described by many authors [1,2,5,7,14]. 37 % of the total milk yield) was produced in the period between 306 and 547 days.…”
Section: Methodsmentioning
confidence: 99%
“…Abdelsayed et al [18] found out the milk yield of 8887 kg produced in the period between 305 to 610 days, with the range 2 891-19 631 kg milk. Holstein cattle from various countries reached different milk yield per lactation [4,5,17]. Table 4 shows that the milk yield per partial 100-day periods decreased with progressing lactation and the indices of persistence, based on the partial milk yields, copied Our values of IP2:1 were considerably higher because the initial dataset included the data on extended lactations (up to 732 days) in which milk yield started to decline later in lactation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these cases, it is common to find no recordings, or at most one recording, made before the peak yield, which makes the estimation of the cell proliferation phase of lactation and peak yield less accurate (Fathi Nasri et al, 2008). Sitkowska et al (2020) found that Wood's and Wilmink's are among the best models for modeling lactation curves; however, a different model may present a better fit depending on the type and homogeneity of data.…”
Section: Model Dynamics and Estimates Of Equation Parametersmentioning
confidence: 99%